PERSEPSI PETANI TERHADAP KEBIJAKAN PENGEMBANGAN AGRIBISNIS TANAMAN BAWANG MERAH DI KELURAHAN BANTURUNG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - Roky Mandaraga; Revi Sunaryati; Eka Nor Taufik (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
This research was conducted to find out how big the level of farmers' perceptions of the onion agribusiness development policy. The author uses a Likert scale for the basis of calculations. This research was conducted in Banturung Village, Bukit Batu Subdistrict, Palangka Raya City. The results of the study consisted of: in terms of program assistance in the